Custeio baseado em atividades e balanced scorecard em um estudo de caso na área de assistência médica domiciliar - Gaspar, Désirée Michels Cortez (2003)
As part of brazilian culture which uses to import business models, international sceneries, social economic circunstances without too much market analysis, assistência médica domiciliar carne to Brazil in the early 90 s. In some cases assistência médica domiciliar carne integrated, but in most cases it carne isolated and speciaiized. Either ways, it becarne evident a poor hability to 100k this businees as a speciaiized professionals services rendered and so, as a service which offers added value and deserves to be rewarded for that. Apart from some comments, Homecare is about to be regulated by 2004. This means almost 14 years in which Homecare has been without tough requirernents and where ABEMID - Brazilian homecare medical association - tried to promote rnodels, standards, directions with their Homecare patients, care givers, drivers, suppliers, etc. But it was clearly detected that the business, in some companies, needed a further professional management. This work tries to contribute towards this necessity. lt introduces, in a first moment, homecare definition, threatens and opportunities on the national and international social econornical scenery. Using management business tools, it is presented a way of measuring performance and and cost. Then results are presented and, from them, management fact based suggestions, different from the current ones, are pointed out. Above ali, the biggest contribution brought with this work is based on business proposed tools that rnight be applied in the company, business unit or the business itself from today. Tools that can t be expected to be a success, but that can, for sure, set bounds for ali the work done since then.